Cross-border Waters in Asia - Luo, Huiling (Sinología hispánica. China Studies Review, 2020)
The high concentration of transboundary waters in China and the dependence that the riparian countries have on these waters, as well as their economic growth and *the* changes in water cycles due to climate change, make transboundary water management a first order task for the Chinese government. This document analyzes the main transboundary river basins in China and the unresolved problems of transboundary waters. Finally, the agreements, treaties and memoranda in force, which help to maintain a certain atmosphere of dialogue, to avoid future military confrontations, especially between countries that are nuclear powers such as China, India and Pakistan.